Penerapan Model Pembelajaran Berbasis Masalah untuk Meningkatkan Hasil Belajar Matematika Materi Pecahan Pada Siswa Kelas IV SDIT Baitul Qur’an Panti - Hidayah, Atika; Marfu'i, Lucky Nindi Riandika (Jurnal Inovasi Pendidikan Dan Pembelajaran, 2025)
This study aims to describe the implementation of the Problem-Based Learning (PBL) model in mathematics learning on fraction material and to determine the improvement in student learning outcomes after its application. This research is a Classroom Action Research (CAR) conducted in class IV of SDIT Baitul Qur’an Panti with 15 student participants. The study was carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The instruments used included learning outcome tests, observation sheets, and teacher reflection sheets. The results showed that the implementation of the PBL model improved student learning outcomes. The average score increased from 58.67 in the pre-cycle to 72.00 in the first cycle and 86.67 in the second cycle. Learning mastery improved from 26.67% in the pre-cycle to 66.67% in the first cycle and 93.33% in the second cycle. This research contributes to the development of educational science, particularly in the application of innovative learning models that enhance contextual and meaningful understanding of mathematical concepts.